2018
DOI: 10.4049/jimmunol.1701121
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient and Versatile Plasmid-Based Gene Editing in Primary T Cells

Abstract: Adoptive cell transfer (ACT) is an important approach for basic research and emerges as an effective treatment for various diseases including infections and blood cancers. Direct genetic manipulation of primary immune cells opens up unprecedented research opportunities and could be applied to enhance cellular therapeutic products. Here, we report highly efficient genome engineering in primary murine T cells using a plasmid-based RNA-guided CRISPR system. We developed a straightforward approach to ablate genes … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 35 publications
4
32
1
Order By: Relevance
“…24 In addition, viral delivery and expression of gene-editing machinery require the target cells to be cultured for several days before the desired gene is edited, potentially losing the naïve phenotype of the target cell. A recent study showed that simply delivering plasmids that encode the gene editing machinery could efficiently target genes in T cells, 32 however, our data suggest that even highly activated NK cells are inefficient at transcribing the required genes from large plasmid templates to result in Cas9-mediated editing. It is worth noting that pMAX-GFP vector uses a CMV promoter and at 3486 bp is considerably smaller than the Px458 (9300 bp), which uses a Cbh promoter.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…24 In addition, viral delivery and expression of gene-editing machinery require the target cells to be cultured for several days before the desired gene is edited, potentially losing the naïve phenotype of the target cell. A recent study showed that simply delivering plasmids that encode the gene editing machinery could efficiently target genes in T cells, 32 however, our data suggest that even highly activated NK cells are inefficient at transcribing the required genes from large plasmid templates to result in Cas9-mediated editing. It is worth noting that pMAX-GFP vector uses a CMV promoter and at 3486 bp is considerably smaller than the Px458 (9300 bp), which uses a Cbh promoter.…”
Section: Discussioncontrasting
confidence: 58%
“…A recent report demonstrated that T cells could be efficiently gene‐edited by simply introducing plasmids that contain Cas9 and the gRNA (transient transfection), 32 and if applicable to NK cells, would represent the most rapid and cost‐effective method of gene‐editing. We therefore cloned one of our validated guides against human CD45 (guide #61) into the Px458 "all‐in‐one" vector 29 that encodes Cas9 gene, eGFP, and the sgRNA.…”
Section: Resultsmentioning
confidence: 99%
“…For this purpose, we transfected 10 6 primary B cells with 2 μg plasmid DNA encoding for a CMV promoter-driven GFP reporter gene directly after isolation from a mouse spleen or following pre-activation on 40 LB feeder cells for 1, 2, 3, or 4 days and analyzed GFP expression by flow cytometry 24 h after transfection. We observed enhanced transfection efficiencies and viability after pre-activation compared to transfection of freshly isolated B cells, consistent with previous findings in primary T cells (49). The highest transfection efficiency was observed after 1 day of pre-activation, followed by 4 days of pre-activation, suggesting a correlation with the time points of high proliferation rates.…”
Section: Resultssupporting
confidence: 92%
“…We observed robust transfection efficiencies (electroporation by nucleofection) in primary B cells following pre-activation and expansion on fibroblast feeder cells expressing BAFF and CD40 ligand. Cas9-RNP-mediated HDR of double-stranded DNA occurred consistently, but with relatively low efficiencies when compared to other primary lymphocyte cells, such as T cells (49, 59). Furthermore, in contrast to observations in multiple other cell types including T and stem cells, AAV delivery of the HDR donor only marginally increased HDR frequencies in primary B cells, suggesting that low HDR efficiencies are independent of template format and transfection efficiencies (52, 58).…”
Section: Discussionmentioning
confidence: 91%
“…S10B, we could observe reduced frequencies of SMARTA SLAM lo CXCR5 + T FH cells or BCL6 + CXCR5 + GC-T FH cells in mice receiving SMARTA CD4 + T cells retrovirally transduced with shTOX-expressing vector compared to the ones with pMDH control vector. Moreover, when Tox was disrupted through using a recently established plasmid-based RNA-guided CRISPR system ( 28 ), further decreases in both T FH and GC-T FH cells could be observed (Fig. 5, A and B).…”
Section: Resultsmentioning
confidence: 94%